The state of web accessibility for people with cognitive disabilities: a rapid evidence assessment - Gartland, Sara (2022)
Increased digitisation of day-to-day activities was occurring prior to the COVID-19 pandemic. The pandemic only accelerated the virtual shift, making web accessibility an urgent issue, especially for marginalised populations. Despite decades of work to develop, refine, and implement web accessibility standards, people with cognitive disabilities regularly experience many barriers to web accessibility. To inform ongoing work to improve web accessibility for people with cognitive disabilities, a systematic review was conducted. The main question guiding this review is: what are the state-of-the-art of interventions that support web accessibility for citizens, 9 years of age and up, living with cognitive impairment? A set of 50 search strings were entered into three academic databases: SCOPUS, ProQuest, and Web of Science. Systematic screening procedures narrowed the search returns to a total of 45 included papers. A data analysis revealed themes associated with the lived experiences of people with cognitive disabilities, tools for improving web accessibility, and methodological best practices for involving people with cognitive disabilities in research. These findings have immediate implications for ongoing research and the development of meaningful solutions to the problem of web accessibility for people with cognitive disabilities.